THE USE OF TORTURE WHILE INVESTIGATING SUSPECTED TERRORIST - Titahelu, Juanrico A.S.; Ashri, Muhammad; Manuputty, Alma; Napang, Marthen (IJRDO-Journal of Applied Science, 2015)
Efforts to fight terrorism draws seriously attention from states in the world. United Nations draws upseveral Resolutions and Conventions proposed to abolish terrorism. States in the world ratified UN Resolutions andConventions, then enacted it in to their national legislation. Many kind of procedures are practiced by investigatorsto collect informations relating to activity of the suspected terrorist, and enabled to identify and apprehends of otherterrorists, warned of terrorist plots planned for states around the world. Use of torture to investigate suspectedterrorist results a good information for protecting greater civilians. The use of torture and in any proceedings to relyon evidence in the fight against terrorism must be legalized, so that it can be better controlled and regulated. That itsmore better for a terrorist endures sufferring than the slow moving development in humanity manner whileinvestigating the suspected terrorist, so that can emerge other terror accident in other place which could make resultssuffers on other civilianz. Manner like this is not in line with just and civilized humanity principle. Just and civilizedhumanity has a significant meaning for the life of the whole society, includes for the suspected terrorist self.Civilized manner investigations must be practized without result suffer to and disappears the life of suspectedterrorist.The purpose of this writing aims to get theoretical view about the use of the method based on just andcivilized humanity while investigates a suspected terrorist. Writings method have the descriptive and analitcalquality which compares the utilitarian manner to just and civilized humanity.